Could AGEs be markers of pre-eclampsia? Study of concentration of advanced protein glycation products in pregnant women with physiological pregnancy and pregnancy complicated with pre-eclampsia - Piotr Bodzek; Iwona Janosz; Aleksandra Damasiewicz-Bodzek; Łukasz Witek; Anita Olejek (Śląski Uniwersytet Medyczny w Katowicach, 2022)
Introduction The role of advanced glycation end products (AGEs) in the pathomechanism of arterial hypertension has been demonstrated, but little information is available on the influence of AGEs on the course of pre-eclampsia (PE). The aim of the study was to assess the concentration profile of advanced protein glycation products in pregnant women diagnosed with PE. Material and methods The concentrations of AGEs, carboxymethyllysine (CML), carboxyethyllysine (CEL) and methylglyoxal (MG) in the sera of female respondents were determined using the enzyme immunoassay method. Results The levels of AGE and CML were lower in the group of women with PE compared to the group of non-pregnant women (p = 0.0411 and p = 0.0072). A lower CML concentration was found in healthy pregnant women as compared to healthy non-pregnant women (p = 0.00068). Positive correlations were found between AGE and CML levels in women with PE (R = 0.339, p = 0.032) and between CML and CEL in healthy non-pregnant women (R = 0.447, p = 0.012). Conclusions We suggest that there is a decrease in the intensity of non-enzymatic protein glycation during pregnancy. Moreover, our study indicates that isolated PE may be associated with a different pathomechanism than chronic hypertension, and therefore AGEs cannot be at present considered a marker of PE.